Religiosity and Social Support as Predictors for Subjective Well-Being of Overseas Students during Pandemic - Fenti Hikmawati; Hermia Santika; Nisa Hermawati (Psympathic : Jurnal Ilmiah Psikologi, 2022)
The Covid-19 pandemic, which led to the wide use of online services to conduct lectures and other academic-related services, negatively impacted the well-being of overseas students. Therefore, it is necessary to have predictors that can increase their subjective well-being (SWB). The purpose of this study is to determine the effect of religiosity and social support on SWB of overseas students during the pandemic. A quantitative correlational study was employed with data collected from 100 people aged 18-25 through a purposive sampling technique. The SWB of the respondents were measured to determine their religiosity, social support, the Positive and Negative Affect Schedule (PANAS), as well as Life Satisfaction scales. The multiple linear regression analysis results showed that religiosity and social support simultaneously significantly affected students' SWB during the pandemic, while social support partially affected SWB.